Implementation of the Flipped Classroom Model to Improve Student Learning Outcomes - Tomasouw, Jolanda; Marantika, Juliaans E. R.; Que, Stella R.; Van Delzen, June C. Noya (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2024)
This study investigates how implementing the Flipped Classroom model can improve high school students' German language learning outcomes at Lab Unpatti High School. The Flipped Classroom is a blended learning approach combining face-to-face interaction with online activities, integrating synchronous (real-time) learning with asynchronous (self-paced) study. This model moves the initial information delivery outside the classroom, allowing class time to be used for deeper knowledge assimilation. The study involved 24 tenth-grade students from Lab Unpatti High School. An experimental method with a one-group pre-test and post-test design was employed. Data collection instruments included tests and questionnaires. Data analysis using a t-test showed that the calculated t-value (5.055) significantly exceeded the t-table value (1.710). This significant difference indicates a substantial improvement in learning outcomes, with students' average German scores increasing by over 89%. Therefore, it can be concluded that the Flipped Classroom model effectively enhances students' learning outcomes.